Difference in DNA Methylation between Cleft Lip and Cleft Lip and Palate - Ruby Riana Asparini; David S. Perdanakusuma; Retno Handajani; Henydhar Bramastivira Mahdani; Sulistyo Mulyo Agustini (Indian Journal of Forensic Medicine & Toxicology, 2022)
It is suspected that environmental exposure to non-syndromic oral clefts, which includes cleft lip (CL), cleft lip and palate (CLP) has an effect on epigenetic mechanisms, particularly deoxyribonucleic acid (DNA) methylation. DNA methylation will be expressed during facial morphogenesis and have an impact on facial development. This study aimed to observe differences in DNA methylation between CL and CLP, between CL mothers and CLP mothers, and correlation between CL and CL mothers, CLP and CLP mothers.This observational study used a sample of 13 patients diagnosed with CL and 14 patients diagnosed with CLP and their respective mothers. The test was performed using ELISA MethylFlashTM Global DNA Methylation (5-mC) ELISA Easy Kit (Colorimetric).The median DNA methylation at CLP was 1.92 (0.23 - 14.07) and CL was 1.71 (0.08 - 8.47) (p 0.752 > 0.05)). Median DNA methylation in CLP mothers was 0.997 (0.03 - 6.14) and in CL mothers 0.72 (0.23 - 6.16) (p 0.798 (p> 0.05). Correlation test for DNA methylation of CLP with CLP mother r = -0.259 and (p = 0.394 >0.05). Correlation test for DNA methylation of CL patients with CL mothers revealed r = -0.492 and (p = 0.087 > 0.05).The results of this study showed no difference in methylation between CL and CLP. This study found that DNA methylation between CL mothers and CLP mothers was relatively the same. This study also found no correlation between DNA methylation of CL and CL mothers, and between CLP and CLP mothers.